Avoiding Mistakes While Writing Scientific Manuscripts In Health Sciences - Faddi Ghassan Saleh Velez; Camila Pinto Bonin; Maria Regina Chalita; Denise Pinheiro Falcão; Felipe Fregni; Rivadávio Fernandes Batista de Amorim (Brazilian Society of Geriatrics and Gerontology, 2024)
INTRODUCTION: This article is part of a special series designed to help authors in the process of scientific writing. OBJECTIVE: To address common mistakes that researchers commit while writing a manuscript, in order to understand and optimize the process of writing a new research paper. METHODS: The authors made a nonsystematic search in the current literature (PubMed) to retrieve papers that address the most frequent mistakes found by editors, peer reviewers, journals and authors. RESULTS: According to the search results, key findings about the most common mistakes for each section of a manuscript were described (introduction section, methods section, results section, discussion section, conclusion section, references, title and abstract). CONCLUSION: There is a great amount of avoidable mistakes in each section of a scientific manuscript. Overall, among the most common mistakes are missing data, incomplete sections, excessive report of current literature or reporting data in an inadequate section.